Not all is lost: resilience of microbiome samples to freezer failures and long-term storage - M. Fabiola Pulido Barriga; James W. J. Randolph; Sydney I. Glassman (mSphere)
ABSTRACT Advances in technology have facilitated extensive sample collection to explore microbiomes across diverse systems, leading to a growing reliance on ultracold freezers for storing both samples and extracted DNA. However, freezer malfunctions can jeopardize data integrity. To evaluate the impact of an unexpected −80°C freezer failure and the recoverability of thawed soil samples, we extracted DNA and compared it to long-term DNA stored at −20°C and original 16S and ITS2 sequencing data collected before the malfunction. Using Illumina MiSeq, we assessed how the freezer failure and long-term storage influenced the resilience of bacterial or fungal richness or community composition and our ability to accurately determine experimental treatment effects. Our results reveal substantial resilience in fungal richness and both bacterial and fungal beta-diversity to soil sample thawing and extended frozen DNA storage. This resilience facilitated biological inferences that closely mirrored those observed in the original study. Notably, fungi exhibited greater resilience to short-term thawing compared to bacteria, which showed sensitivity to both thawing and long-term freezing. Moreover, taxonomic composition analysis revealed the persistence of dominant microbial taxa under thawing and prolonged freezing, suggesting that dominant microbes remain viable for tracking across temporal studies. In conclusion, our study highlights that beta-diversity is more robust than alpha-diversity and fungi are more resilient to freezer failure than bacteria. Furthermore, our findings underscore the effectiveness of soil storage at −80°C compared to storage of extracted DNA at −20°C, despite potential freezer failures, as the most robust method for long-term storage in microbiome studies.IMPORTANCEMicrobiome studies heavily rely on ultracold freezers for sample storage. Unfortunately, these freezers are prone to frequent malfunctions, resulting in the loss of invaluable samples at laboratories worldwide. Such losses can halt research progress due to potential issues with sample reliability. Our research demonstrates that not all is lost when an unforeseen freezer failure occurs. Samples can still be reliably used to assess treatment effects, which is particularly important for long-term temporal studies where samples cannot be readily obtained again.